Allegorical painting of the birth of Louis Joseph, Dauphin of France... - François-Guillaume... (Wikimedia Commons)
Notice iconographique issue de Wikimedia Commons. Titre: Allegorical painting of the birth of Louis Joseph, Dauphin of France, 22 October 1781.
Licence Public domain via Wikimedia Commons
Keywords: œuvre d'art; tableau; sculpture; statue; wikimedia commons